2013
DOI: 10.1155/2013/708362
|View full text |Cite
|
Sign up to set email alerts
|

Penile Fracture: Experience from a Third World Country

Abstract: Aim. To ascertain the clinical presentation, commonest age group affected, and treatment of patients diagnosed to have penis fracture. Materials and Methods. We performed a retrospective study carried at a tertiary care hospital from January 2005 to January 2011. All the 36 patients diagnosed to have penile fracture were enrolled in the study group. The diagnosis was made based on the clinical findings in the patients. All, except two patients, were managed by a standard surgical procedure, same for all the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…Penile fracture is the tearing of the tunica albuginea from the corpus cavernosa [8]. The tunica albuginea is among the toughest of body fascias.…”
Section: Discussionmentioning
confidence: 99%
“…Penile fracture is the tearing of the tunica albuginea from the corpus cavernosa [8]. The tunica albuginea is among the toughest of body fascias.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Injury at the time of coitus is regarded as the most common predisposing factor for penile fracture. [6]…”
Section: Discussionmentioning
confidence: 99%
“…[5] Literature from India showed that vaginal intercourse is the most common cause of penile fracture. [6] We in the tertiary care hospital in North East part of India observed penile manipulation as the most common etiology of penile fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Penile fracture is a urological emergency [1]. Penile fracture is defined as a traumatic rupture of the tunica albuginea of the corpora cavernosa with or without the corpus spongiosum, secondary to blunt trauma of an erect penis, a resultant corporal defect caused by trauma to the erect penis [2] [3]. Estimated incidence of penile fracture is about 500 -660 cases per year in the USA [4].…”
Section: Introductionmentioning
confidence: 99%